Donor heart selection and outcomes: an analysis of over 2,000 cases - Aliabadi-Zuckermann, Arezu Z.; Gökler, Johannes; Kaider, Alexandra; Riebandt, Julia; Moayedifar, Roxana; Osorio, Emilio; Haberl, Thomas; Angleitner, Phillipp; Laufer, Günther; Forsythe, John; Knezevic, Ivan; Skoric, Bosko; et al. (The journal of heart and lung transplantation, 2018)
Background - Decision-making when offered a donor heart for transplantation is complex, and supportive data describing outcomes according to acceptance or non-acceptance choices are sparse. Our aim was to analyze donor heart acceptance decisions and associated outcomes at a single center, and after subsequent acceptance elsewhere. - Methods - This investigation was a retrospective analysis of data obtained from the University of Vienna Medical Center and Eurotransplant centers for the period 2001 to 2015. - Results - Our center accepted 31.8% (699 of 2,199) of donor hearts offered. Unlike other centers, the acceptance rate, with or without transplantation, did not increase over time. Of the donor hearts rejected by our center, 38.1% (572 of 1,500) were later accepted elsewhere. Acceptance rates were twice as high for donor hearts initially rejected for non-quality reasons (339 of 601, 56.4%) compared with initial rejection for quality reasons (233 of 899, 25.9%). Three-year patient survival rate was 79% at Vienna; for donor hearts initially rejected by Vienna for non-quality reasons or quality reasons, it was 73% and 63%, respectively (p < 0.001). Outcomes at other centers after transplantation of grafts rejected by Vienna varied according to the reason for rejection, with good 3-year survival rates for rejection due to positive virology (77%), high catecholamines (68%), long ischemic time (71%), or low ejection fraction (68%), but poor survival was observed for hearts rejected for hypernatremia (46%), cardiac arrest (21%), or valve pathology (50%). - Conclusions - A less restrictive policy for accepting donor hearts at our center, particularly regarding rejection for non-quality reasons or for positive virology, high catecholamine levels, longer ischemic time, or low ejection fraction, could expand our donor pool while maintaining good outcomes.